Tm7sf2 Disruption Alters Radial Gene Positioning in Mouse Liver Leading to Metabolic Defects and Diabetes Characteristics - Gatticchi, Leonardo; de las Heras, Jose I.; Sivakumar, Aishwarya; Zuleger, Nikolaj; Roberti, Rita; Schirmer, Eric C. (Frontiers in Cell and Developmental Biology, 2020)
Tissue-specific patterns of radial genome organization contribute to genome regulation and can be established by nuclear envelope proteins. Studies in this area often use cancer cell lines and it is unclear how well such systems recapitulate genome organization of primary cells or animal tissues; so we sought to investigate radial genome organization in primary liver tissue hepatocytes. Here we have used a NET47/Tm7sf2-/- liver model to show that manipulating one of these nuclear membrane proteins is sufficient to alter tissue-specific gene positioning and expression. Dam-LaminB1 global profiling in primary liver cells shows that nearly all the genes under such positional regulation are related to/ important for liver function. Interestingly, Tm7sf2 is a paralog of the HP1-binding nuclear membrane protein LBR that, like Tm7sf2, also has an enzymatic function in sterol reduction. Fmo3 gene/locus radial mislocalization could be rescued with human wild-type, but not TM7SF2 mutants lacking the sterol reductase function. One central pathway affected is the cholesterol synthesis pathway. Within this pathway both Cyp51 and Msmo1 are under Tm7sf2 positional and expression regulation. Other consequences of the loss of Tm7sf2 included weight gain, insulin sensitivity, and reduced levels of active Akt kinase indicating additional pathways under its regulation, several of which are highlighted by mispositioning genes. This study emphasizes the importance for tissue-specific radial genome organization in tissue function and the value of studying genome organization in animal tissues and primary cells over cell lines.